Vascular calcification location, formation and biological activity - Proudfoot, Diane (Henry Stewart Talks, 2014)
Overview of the blood vessel wall, Atherosclerosis, The regulation of Vascular Calcification, including in vivo models, Inhibitors and triggers of Calcification, In vitro models of vascular calcification, The role of apoptosis in calcification, The role of matrix vesicles in calcification, How do mineral deposits affect cells in the blood vessel wall?